2008
DOI: 10.1086/528714
|View full text |Cite
|
Sign up to set email alerts
|

Strong Correlation between Serum Aspergillus Galactomannan Index and Outcome of Aspergillosis in Patients with Hematological Cancer: Clinical and Research Implications

Abstract: We conclude that serum GMI is a good marker of aspergillosis outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
86
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(96 citation statements)
references
References 46 publications
5
86
0
5
Order By: Relevance
“…Success was defined in these studies as a repeatedly negative serum GM in the absence of new extrapulmonary lesions and failure as a persistently positive GM level or death within 2 weeks of GM normalization unless autopsy failed to show evidence of IA. A review of 27 studies of serial GM screening for the diagnosis of IA in hematologic malignancy and HSCT patients also found a correlation between GM levels in the week preceding IA outcome and clinical outcome (15). A simple correlation, however, is insufficient for establishing surrogacy; measurements that correlate with the outcome of interest are not useful surrogates unless they also capture the net effects of treatment on outcome (19,25).…”
mentioning
confidence: 99%
“…Success was defined in these studies as a repeatedly negative serum GM in the absence of new extrapulmonary lesions and failure as a persistently positive GM level or death within 2 weeks of GM normalization unless autopsy failed to show evidence of IA. A review of 27 studies of serial GM screening for the diagnosis of IA in hematologic malignancy and HSCT patients also found a correlation between GM levels in the week preceding IA outcome and clinical outcome (15). A simple correlation, however, is insufficient for establishing surrogacy; measurements that correlate with the outcome of interest are not useful surrogates unless they also capture the net effects of treatment on outcome (19,25).…”
mentioning
confidence: 99%
“…In this setting, the detection of positive results, particularly in two consecutive serum samples, provides strong support for the diagnosis of IA [von Eiff et al 1995;Mennick-Kersten and Verweij, 2006;Maertens et al 2001]. Recently, some authors have also suggested that GM could serve as a surrogate marker of clinical response to treatment in patients with IA [Miceli et al 2008;Maertens et al 2009;Boutboul et al 2002]. Several studies showed that the titer of GM tends to decrease in cases that demonstrated a clinical response.…”
Section: Therapeutic Advances In Infectious Disease 1 (3)mentioning
confidence: 93%
“…We and others recognize that more study is needed to better define the role of this biomarker, knowing that further confirmation of this strong correlation will have significant implications for patient management and clinical trial design. 24,25 …”
mentioning
confidence: 99%